INTENSITAS PERDAGANGAN DAN KESELARASAN SIKLUS BISNIS DI ASEAN-4 DAN UNI EROPA * - Lestari, Etty Puji (Jurnal Ekonomi Pembangunan: Kajian Masalah Ekonomi dan Pembangunan, 2011)
The main objective of this research is to empirically analyze how the business cycle of ASEAN-4 (namely Indonesia, Malaysia, Thailand, and Philippines) economies are influenced by increased trade with European Union especially Netherland and Germany. Increased trade can lead business cycles across trading partners to be patterned in either direction, towards convergence or divergence. We used regression and vectorautoregression (VAR) methods for this research. Regression methods is based panel data whereas VAR is based on the time series analysis. There are four variables, which are business cycle, trade intensity, fiscal policy coordination and monetary policy coordination. This research conclude that trade intensity and monetary policy coordination are the major channel though which the business cycles of ASEAN-4 economies become synchronized. This has important implications for the formation of a currency union.